The Efficacy and Safety of Empagliflozin in Elderly Patients with Type 2 Diabetes Mellitus Complicating Cardiorenal Syndromes Type II and IV: Evaluation of Empagliflozin in CRS - Cao, Mugen; Lin, Qiuyan; Lin, Liling; Zhang, Wenjie; Zhang, Lifeng (Journal of Medical Biochemistry, 2025)
Objectives: Cardiorenal syndrome (CRS) is a complex clinical condition, leading to a deterioration in both cardiac and renal functions. Empagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, is a novel anti-diabetic drug, which also improves cardiac and renal functions. However, there is little research on the efficacy and safety of empagliflozin in elderly type 2 diabetes mellitus (T2DM) patients with CRS. We aimed to evaluate the efficacy and safety of empagliflozin in elderly patients with T2DM complicated by Type II and IV CRS.Methods: A randomized, prospective study was conducted involving 200 elderly patients diagnosed with T2DM and CRS, admitted to the cardiovascular department of Fujian Provincial Governmental Hospital from January 2020 to January 2024. Patients were randomized into an experimental group (n=100) treated with empagliflozin 10mg/day and a control group (n=100) receiving standard care. Blood glucose, cardiac and renal function indicators, adverse reactions and major adverse cardiovascular events were compared between groups. T-tests, Mann-Whitney U tests, Wilcoxon signed-rank tests, and chi-square tests were performed appropriately.Results: After one-year follow-up, patients in the experimental group showed significant improvements in fasting blood glucose, glycated hemoglobin, serum creatinine, urinary microalbumin, NT-proBNP, left ventricular ejection fraction, and left ventricular end-diastolic diameter compared to the control group (P
Keywords: Cardiorenal Syndrome; Type 2 Diabetes Mellitus; Empagliflozin; SGLT2 Inhibitors; Glycemic Control; Cardiorenal Protection